Social Exclusion of Dalits in India: - (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Millions of human beings the world over survive in conditions of poverty and social exclusion, and this is unlikely to change in the years to come. This grave situation affects the whole of humanity, which cannot and must not shut its eyes to it. While it lasts, we will all be somewhat impoverished and, in a certain manner, excluded. This paper has been written to study the social exclusion and its impact on Dalits in India. In the post reform era, India has done well in some economic indicators such as economic growth, exports, stock markets etc, but it was found exclusion in terms of agriculture, growth, low productivity, low employment, rural urban divide etc. Therefore, social exclusion is taking place in terms of region, social, women and children. But the term “social exclusion” has been in the field of intellectuals and policy planners. They used this term to identify the gap between those people who are neglected by the society on the basis of development. This paper highlights the social exclusion and its impact on Dalits in India. This study is based on secondary data which has been collected through journals, websites, newspapers and India exclusion reports etc.